Simulation of Chloride Ingress through Surface-Coated Concrete during Migration Test Using Finite-Difference and Finite-Element Method - Seyoon Yoon (International Journal of Polymer Science)
Polymer surface coatings are commonly used to enhance the corrosion resistance of concrete structures in saline environments to ionic diffusivity; this diffusivity can be determined by migration tests. This paper presents the simulation of the effects of the surface coatings on migration tests by solving the Nernst-Planck/Poisson model using both finite-difference method and finite-element method. These two numerical methods were compared in terms of their accuracy and computational speed. The simulation results indicate that the shapes of ionic profiles after migration tests depend on the effectiveness of surface coatings. This is because highly effective surface coatings can cause a high ionic concentration at the interface between coating and concrete. The simulation results were also compared to homogenized cases where a homogenized diffusion coefficient is employed. The result shows that the homogenized diffusion coefficient cannot represent the diffusivity of the surface-coated concrete.